The Popular Policeman and Other Cases Psychological Perspectives on Legal Evidence - Wagenaar, Willem Albert (Amsterdam University Press, 2005)
In this compelling title, two distinguished scholars share their experiences as expert witnesses in cases ranging from eyewitness testimony, person identification and recovered memories, to false confessions, collaborative storytelling and causal attribution, in the context of various interrogation techniques and their ability to deliver reliable results. Each chapter describes in lucid, entertaining prose a representative case in the context of scholarly literature to date, showing how psychological expertise has been (and can be) used in a legal setting. The cases include petty and serious crime, from illegal gambling, infringed trademarks and risqué courtship behaviour, to honour killing and death on the climbing wall. The authors' findings and recommendations apply to legal systems worldwide. There is no other English-language textbook covering a similarly wide range of offences, and this volume will fill a gap in the existing literature and demonstrate how psychological expertise can be used in a much larger area than is often realised.